Osteoarthritis year in review 2016: imaging. Issue 2 (February 2017) - Boesen, M.; Ellegaard, K.; Henriksen, M.; Gudbergsen, H.; Hansen, P.; Bliddal, H.; Bartels, E.M.; Riis, R.G.
Summary: Purpose: The current narrative review covers original research related to imaging in osteoarthritis (OA) in humans published in English between April 1st 2015 and March 31st 2016, in peer reviewed journals available in Medline via PubMed (http://www.ncbi.nlm.nih.gov/pubmed/ ). Methods: Relevant studies in humans, subjectively decided by the authors, contributing significantly to the OA imaging field, were selected from an extensive Medline search using the terms "Osteoarthritis" in combination with "MRI", "Imaging", "Radiography", "X-rays", "Ultrasound", "Computed tomography", "Nuclear medicine", "PET-CT", "PET-MRI", "Scintigraphy", "SPECT". Publications were sorted according to relevance for the OA imaging research community with an emphasis on high impact special interest journals using the software for systematic reviewswww.covidence.org . Results: An overview of newly published studies compared to studies reported previous years is presented, followed by a review of selected imaging studies of primarily knee, hip and hand OA focussing on (1) results for detection of OA and OA-related pathology (2) studies dealing with treatments and (3) studies focussing on prognosis of disease progression or joint replacement. A record high number of 1420 articles were published, among others, of new technologies and tools for improved morphological and pathophysiological understanding of OA-related changes in joints. Also, imaging data were presented of monitoring treatment effect and prognosis of OA progression, primarily using established radiographic, magnetic resonance imaging (MRI), and ultrasound (US) methods. Conclusion: Imaging continues to play an important role in OA research, where several exciting new technologies and computer aided analysis methods are emerging to complement the conventional imaging approaches.